Penilaian dan Pemetaan Status Keberlanjutan Kota di Provinsi Banten - Asti Istiqomah; Yolamalinda Yolamalinda; Laili Fuji Widyawati (Institut Pertanian Bogor, 2023)
The world population is proliferating, and the proportion of people living in urban areas is also increasing. It is challenging to achieve the SDGs, especially SDG 11, which aims to make cities and communities more inclusive, safe, resilient, and sustainable. Meeting the needs of urban residents, such as housing, public infrastructure, a clean environment, security, jobs, and other basic needs to live comfortably in a city with limited resources, is a problem. Sustainable cities are becoming increasingly important today to facilitate the growth of sustainable cities that integrate economic, sociocultural, environmental, ICT/transverse, and urban dimensions. Effective evaluation of urban sustainability is essential for sustainable development. Banten Province is one of the regions that has committed to achieving the SDGs. This commitment is contained in Banten Governor Regulation Number 47 of 2019 concerning the Regional Action Plan for the Sustainable Development Goals of Banten Province for 2020‒2022. Therefore, this study aims to assess and map the sustainability status of cities in Banten Province using Multi-Criteria Decision Analysis (MCDA) analysis and processed with PROMETHEE (Preference Ranking Organization METHods for Enrichment Evaluation). The number of criteria for a sustainable city in 2012 was 82 criteria and 109 criteria in 2022, where the highest number of criteria is on the sociocultural and economic dimensions. The PROMETHEE results show that the cities in Banten Province with the best sustainability levels are Tangerang City and South Tangerang City. City governments with low sustainability status or experiencing a decrease in sustainability status need to improve the performance of sustainable city indicators so that development can be sustainable. Keywords: ecology, economics, evaluation, preference ranking organization methods for enrichment evaluation, social